Development potential and prospects of Azerbaijan's food industry - Shahin Sadikhov (Economics, Management and Sustainability)
Purpose. This study aims to evaluate the development potential of Azerbaijan’s food industry and identify future growth directions. It investigates the effective utilization of this potential and the prospective development of the industry. Methodology. The research employs statistical and comparative analysis, logical conclusion, and balance methods. It assesses the state of the food industry, examines leading enterprises in the field, analyzes the raw material base of production, and scrutinizes the structure and volume of local production and import. Results. The study reveals that despite the significant weight of the food industry among processing industry fields in Azerbaijan, most domestic demand for food products is met by imports. It proposes measures to effectively use the development potential of the food industry, including protecting the internal market, solving water supply issues, establishing meat and milk collection centers, and more. Theoretical Contribution. This research contributes to the understanding of the economic development potential of the food industry in Azerbaijan. It provides a comprehensive analysis of the current state of the industry and offers practical recommendations for future growth. Practical Implications. The findings of this study have practical implications for policymakers, researchers and industry stakeholders. They provide a roadmap for enhancing the competitiveness of Azerbaijan’s food industry, reducing import dependence, and promoting sustainable economic development.